1994
DOI: 10.1002/1097-0142(19940501)73:9<2296::aid-cncr2820730910>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary infiltrations in febrile patients with neutropenia. Risk factors and outcome under empirical antimicrobial therapy in a randomized multicenter study

Abstract: Background. Different empirical approaches to antimicrobial treatment of lung infiltrates in patients with neutropenia were studied within a prospective, randomized multicenter trial. Methods. Patients with neutropenia with hematologic malignancies and fever of 38.5'C or higher associated with newly diagnosed lung infiltrates were randomized for an initial therapy with acylaminopenicillin plus aminoglycoside (Group A), third-generation cephalosporin plus aminoglycoside (Group B), or the double &lactam combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(64 citation statements)
references
References 69 publications
1
58
1
4
Order By: Relevance
“…Additionally, most neutropenic patients with pneumonia receive antifungal drugs according to international guidelines [16,18,19,26]. It is known that previous antimicrobial treatment lowers the yield of BAL culture and is probably responsible for the low impact on treatment changes [4,5,7,9,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, most neutropenic patients with pneumonia receive antifungal drugs according to international guidelines [16,18,19,26]. It is known that previous antimicrobial treatment lowers the yield of BAL culture and is probably responsible for the low impact on treatment changes [4,5,7,9,30].…”
Section: Discussionmentioning
confidence: 99%
“…Among these infections, pneumonia is a very serious complication and has a poor prognosis, especially if treatment is delayed [10,11,31]. Patients with neutropenia should be treated immediately after onset of fever or any sign of infection and antimicrobial treatment should be initiated according to published guidelines even if positive diagnostic results are still lacking [13,16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Kolbe et al 7 observed a 5% rate of pneumonia in PBSCT patients and Maschmeyer et al 8 showed a rate of pneumonia of around 20% in patients receiving conventional chemotherapy. In our study, pneumonia occurred in 24% of patients in the CCT group.…”
Section: Discussionmentioning
confidence: 99%
“…4 The application of EAT is indicated without delay in patients with severe sepsis or septic shock, or in those with signs of focal infection (pulmonary infiltrates, sinusitis, brain abscess, skin lesions and abdominal focus) in which IFI is an outstanding aetiology. [14][15][16][17][18][19][20][21] In those patients at high risk for fungal infection, when fever and neutropenia persists without an alternative diagnosis, EAT may be indicated through an individualized clinical decision. In the rest of the patients with asymptomatic fever who are clinically stable (which constituted the main clinical syndrome of PFN) with a low IFI incidence (null in our study), EAT would not be applied and further diagnostic evaluation, including high-resolution thorax scan, galactomannan and abdominal ultrasound, should be performed to establish the aetiology of the persistent fever.…”
mentioning
confidence: 99%